Improving processes through the use of the 5S methodology and menu engineering to reduce production costs of a MSE in the hospitality sector in the department of Ancash - Alva, Indira (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.